2015
DOI: 10.1002/jat.3206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulpiride and ethylene glycol monomethyl ether on endometrial carcinogenicity in Donryu rats

Abstract: Sulpiride and ethylene glycol monomethyl ether (EGME) are known ovarian toxicants that stimulate prolactin (PRL) secretion, resulting in hypertrophy of the corpora lutea and increased progesterone (P4) production. The purpose of the present study was to investigate how the PRL stimulatory agents affected uterine carcinogenesis and to clarify the effects of PRL on endometrial adenocarcinoma progression in rats. Ten-week-old female Donryu rats were treated once with N-ethyl-N'-nitro-N-nitrosoguanidine (20 mg kg(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As sulpiride has been shown to inhibit gastric carcinogenesis (Tatsuta et al, 1991) as well as endometrial carcinogenesis (Taketa et al, 2016) in rats, it would be interesting to further test how the potential of sulpiride in inhibiting liver carcinogenesis and how DAPK1 may be involved in future study.…”
Section: Discussionmentioning
confidence: 99%
“…As sulpiride has been shown to inhibit gastric carcinogenesis (Tatsuta et al, 1991) as well as endometrial carcinogenesis (Taketa et al, 2016) in rats, it would be interesting to further test how the potential of sulpiride in inhibiting liver carcinogenesis and how DAPK1 may be involved in future study.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanism of this has not yet been determined; however, the primary MOA was thought to be a decreased E2 to P4 ratio due to the modulation of P4 production by prolactin. Our current work provided interesting evidence demonstrating that short- and long-term treatment with sulpiride, a typical dopamine antagonist, clearly increased serum prolactin 25 and inhibited uterine tumor development 26 . In addition, long-term treatment with sulpiride also decreased the E2 to P4 ratio, indicating that prolactin has various complex functions.…”
Section: Discussionmentioning
confidence: 57%
“…The antifertility effects described for PAs and the identification of PAs in the Emilia genus strongly implicates compound 5 as a potential compound for further study as the active constituent responsible for the antifertility effects observed in this study. Glycols have been reported to exhibit antitumor effects (Wang et al 1996;Taketa et al 2015), anxiolytic effects (Lin et al 1998), and sedative effects in humans (Singh et al 1981;Forrest and Galletly 1988). Reports have shown polyethylene glycol (PEG) to exert inhibitory effects on liver enzymes and on central nervous system activity (Nishimura et al 1998;Thomsen et al 1995).…”
Section: Chromatogram and Biological Effects Of Identified Compoundsmentioning
confidence: 99%